Sosialisasi Pencegahan Covid-19 dalam Upaya Perbaikan Ekonomi Masyarakat desa Kueh Keude Bing - Lilis Maryasih; Nita Erika Ariani; Maya Febrianty L; Linda Linda; Yulia Fitri (Asosiasi Dosen Akuntansi Indonesia, 2021)
As the number of confirmed COVID-19 cases are increasing in Province Aceh, it is necessary to do community service with objective to socialize the proper knowledge of virus and how to apply the preventive measures to protect themself against infections. Particularly for communities with a high risk of virus contagion such as traditional traders. The community needs to be informed and adapt the movement of 3M; wearing a mask, social distancing practices and washing hand on their daily life. This community service was conducted in form of socialization on virus corona information and the distribution of masks and hand sanitizer for the community. This devotin also focuses on driving the traditional economy during the COVID 19 pandemic at Desa Keuh Keude Bing, kecamatan Lhoknga , kabupaten Aceh Besar, Indonesia.